Implementação de sistema de automação no processo de produção de formulados em pó - Huf, Marco Vinicius Fontenele Amorim (2021)
This project was conceived based on the author's experiences during his internship in the powder and pasta industry. One of the operations is the weighing of raw material and the bagging of a predefined mixture according to demand. However, weighing and bagging is done manually, which generates errors that are not considered in the material balance. Automated operations control and data management are essential tools for efficient process management. The present work develops a software and a hardware to acquire production data in the step of weighing the raw material used in the production process of food powders. The System sends the data to a system, which generates reports and accelerates management reactivity to quality and production deviations.